Sustainable residential area development in slum area of Makassar city - Mungkasa, Nirman Niswan; Latief, Muh. Iqbal; Aprianti, Evi (Edelweiss Applied Science and Technology, 2025)
The problem of slum creation remains a significant issue in urban development in Indonesia, including in Makassar City. This study aims to formulate strategies for developing sustainable organizational areas within slum regions in Makassar City, particularly in Tallo, Tanjung Merdeka, and Bontorannu Sub-districts. The research employed a mixed-method approach, utilizing internal and external factor analysis (IFE-EFE), SWOT analysis, and prioritization of strategies. The findings indicated that Bontorannu Village exhibited the highest readiness in terms of physical and institutional aspects, whereas Tallo and Tanjung Merdeka still require improvements in basic infrastructure and community participation. Seven primary strategies were identified, with four prioritized: constructing integrated wastewater treatment plants and drainage systems, increasing access to clean water and fire protection, implementing collaborative waste management, and strengthening local institutions. This study underscores the importance of a collaborative, participatory, and locally contextual approach to achieving habitable, safe, and sustainable settlements.